DNA variation of the mammalian major histocompatibility complex reflects genomic diversity and population history. - Yuhki, N (1990)
The major histocompatibility complex (MHC) is a multigene complex of tightly linked homologous genes that encode cell surface antigens that play a key role in immune regulation and response to foreign antigens. In most species, MHC gene products display extreme antigenic polymorphism, and their variability has been interpreted to reflect an adaptive strategy for accommodating rapidly evolving infectious agents that periodically afflict natural populations. Determination of the extent of MHC variation has been limited to populations in which skin grafting is feasible or for which serological reagents have been developed. We present here a quantitative analysis of restriction fragment length polymorphism of MHC class I genes in several mammalian species (cats, rodents, humans) known to have very different levels of genetic diversity based on functional MHC assays and on allozyme surveys. When homologous class I probes were employed, a notable concordance was observed between the extent of MHC restriction fragment variation and functional MHC variation detected by skin grafts or genome-wide diversity estimated by allozyme screens. These results confirm the genetically depauperate character of the African cheetah, Acinonyx jubatus, and the Asiatic lion, Panthera leo persica; further, they support the use of class I MHC molecular reagents in estimating the extent and character of genetic diversity in natural populations.